2011
DOI: 10.1073/pnas.1014345108
|View full text |Cite
|
Sign up to set email alerts
|

Implicit race attitudes predict trustworthiness judgments and economic trust decisions

Abstract: Trust lies at the heart of every social interaction. Each day we face decisions in which we must accurately assess another individual's trustworthiness or risk suffering very real consequences. In a global marketplace of increasing heterogeneity with respect to nationality, race, and multiple other social categories, it is of great value to understand how implicitly held attitudes about group membership may support or undermine social trust and thereby implicitly shape the decisions we make. Recent behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
210
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(248 citation statements)
references
References 30 publications
(42 reference statements)
17
210
6
1
Order By: Relevance
“…As with other forms of implicit bias (23,30,31), the effect is not always limited to people who explicitly endorse traditional gender-trait beliefs. In experiments 4 and 5, we measured gendertrait beliefs and found that both those who affirmed and those who rejected the notion of differences in men's and women's warmth and aggressiveness based their evacuation intentions on the gendered names.…”
Section: Discussionmentioning
confidence: 98%
“…As with other forms of implicit bias (23,30,31), the effect is not always limited to people who explicitly endorse traditional gender-trait beliefs. In experiments 4 and 5, we measured gendertrait beliefs and found that both those who affirmed and those who rejected the notion of differences in men's and women's warmth and aggressiveness based their evacuation intentions on the gendered names.…”
Section: Discussionmentioning
confidence: 98%
“…We think it is important to make the distinction here between using the implicit association test (IAT) for diagnostic purposes (e.g., to classify individuals as 'racist') and using the IAT for research purposes (i.e., to investigate a potential contributing factor to trust behavior in our study) (2). We emphatically agree with Krueger (1) that, in its current instantiation, the IAT should not be used for diagnostic purposes.…”
mentioning
confidence: 43%
“…We were motivated by evidence for a common neural substrate, but the fact that we found a correlation was not a foregone conclusion. We did not make the claim that one's IAT score was diagnostic of whether one was 'racist' in their trust behavior (2). Trust estimations are complex, and the evidence from our own study (2) and others suggested that they covaried with many factors, both explicit and implicit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stanley et al (1) closed with the causal claim that decisions are partly determined by processes lying outside of awareness and that this "may have a very real cost for individuals and society" (ref. 1, p. 5).…”
mentioning
confidence: 99%